A Review On Analysis Of Market Entry Strategies For Indian Export Oriented Units (Eous) Into Global Markets In Emerging Brics Countries (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to investigate about the trade relationship connecting India and other BRICS nations in both the short and long term. To do so, we begin by assessing the stationarity of variables using the ADF-Fisher unit root test. Subsequently, we apply Pedroni's cointegration test to analyze the relationship between selected variables. Upon confirming stationarity and co integration, we utilize the Granger Causality Test to explore short-term impacts and employ the Gravity Model with for extended analysis, use Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS). The Granger Causality test reveals substantial support for India's trade interactions with other BRICS nations, with a bidirectional causality observed between India's exports and other BRICS countries' imports. Conversely, no causality exists between India's imports and other BRICS nations' exports. Furthermore, the study identifies a positive unidirectional causality between India's GDP and the trade volume of other BRICS nations. In the long term, the Gravity model employs FMOLS and DOLS. demonstrates the significance of certain variables—GDP, per capita GDP (PCGDP), PCGDP differential, distance, trade-to-GDP ratio, and exchange rate —except for Agreements on trade and inflation. Notably, these variables exhibit positive coefficients in relation to BRICS trade volume, indicating a favorable impact on the Indian economy. In conclusion, our analysis affirms the suitability of the Gravity model for assessing trade dynamics. We strongly recommend that India increases trade relations with fellow BRICS countries by encouraging initiatives like "Make in India," Special Economic Zones (SEZs), Export Oriented Units (EOUs), and advancing 2nd-generation reforms. These efforts are essential for maximizing the potential benefits of the global economy.